PWM speed control of dc permanent magnet motor using a PIC18F4550 microcontroller. (August 2019) - Fatma, M W; Hamid, M I
Abstract: The purpose of this design is to study the advantages of controlling the DC motor speed by adjusting the permanent magnet of DC motors. This had been done by applying the PWM method with relay using PIC18F4550 micro-controller. The output signal from each controllers were compared with the control system and describe the output value and data related to the system. The result shows that the PWM method was able to maintain the motor speed better than the continuous voltage method.